Bioprocess Forces and Their Impact on Cell Behavior: Implications for Bone Regeneration Therapy. (23rd August 2011) - Brindley, David; Moorthy, Kishaani; Lee, Jae-Ho; Mason, Chris; Kim, Hae-Won; Wall, Ivan
Abstract : Bioprocess forces such as shear stress experienced during routine cell culture are considered to be harmful to cells. However, the impact of physical forces on cell behavior is an area of growing interest within the tissue engineering community, and it is widely acknowledged that mechanical stimulation including shear stress can enhance osteogenic differentiation. This paper considers the effects of bioprocess shear stress on cell responses such as survival and proliferation in several contexts, including suspension-adapted cells used for recombinant protein and monoclonal antibody manufacture, adherent cells for therapy in suspension, and adherent cells attached to their growth substrates. The enhanced osteogenic differentiation that fluid flow shear stress is widely found to induce is discussed, along with the tissue engineering of mineralized tissue using perfusion bioreactors. Recent evidence that bioprocess forces produced during capillary transfer or pipetting of cell suspensions can enhance osteogenic responses is also discussed.